Asprosin levels in patients with type 2 diabetes mellitus, metabolic syndrome and obesity: A systematic review and meta-analysis - Ulloque-Badaracco, Juan R. (2024)
Background & aims: Asprosin is a promising candidate for novel treatments for metabolic–endocrine disorders. The objective of this systematic review and meta-analysis was to consolidate the existing evidence regarding asprosin levels in patients diagnosed with type 2 diabetes (T2D), metabolic syndrome (MetS), and obesity. Methods: Scopus, Embase, PubMed, Ovid/Medline, and Web of Science were systematically searched without restrictions. We only used the standardized mean differences (SMD) with their 95 % confidence intervals (95 % CI) as the effect measure. A random-effects model (DerSimonian and Laird method) was used for the meta-analysis. Risk of bias was assessed with the Newcastle–Ottawa Scale and Newcastle–Ottawa Scale for Cross-Sectional Studies. Results: Twenty-six studies (n = 3,787) were included in the meta-analysis. Participants with T2D had higher asprosin values than those without T2D (SMD: 1.64; 95 % CI: 1.08–2.21; I2 = 97 %). Patients with MetS had higher asprosin levels compared to those without MetS (SMD: 0.99; 95 % CI: 0.34–1.64; I2 = 96 %). Patients with obesity had higher asprosin levels than participants without obesity (SMD: 1.49; 95 % CI: 0.23–2.76; I2 = 98 %). Conclusions: Asprosin is significantly higher in patients with either T2D, MetS, or obesity, compared with controls.